Uniform family code : the proposal of Bangladesh Mahila Parishad - Nabi, Bela; Bāṃlādeśa Mahilā Parishada (Dhaka, Bangladesh : Bangladesh Mahila Parishad, 2015)
Contributed articles and recommendations for reform and amendments of laws concerning rights of women and uniform family code in Bangladesh as envisaged by the Bāṃlādeśa Mahilā Parishada, or Bangladesh Women Council, during a series of workshops held at various locations countrywide.
Includes bibliographical references (pages 311-328).
GenEd
Book Finder International
Translated from Bengali.
Keywords: Bāṃlādeśa Mahilā Parishada -- Congresses; Women's rights -- Bangladesh -- Congresses; Women -- Legal status, laws, etc. -- Bangladesh -- Congresses; Domestic relations -- Bangladesh -- Congresses